2017
DOI: 10.3892/etm.2017.4877
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol enhances the sensitivity of human ovarian cancer cells to radiotherapy-induced apoptosis due to downregulation of the phosphatidylinositol-3-kinase/Akt/phosphatase and tensin homolog pathway and inhibition of vascular endothelial growth factor

Abstract: Abstract. Radiotherapy is a vital and effective method to treat solid tumors. However, in many tumor types, development of resistance of cancer cells and cytotoxicity in normal tissues presents a major therapeutic problem. It is therefore crucial to identify and develop novel sensitizing agents that may improve the response to radiation therapy without causing any adverse effects. The present study aimed to investigate whether paeonol, a bioactive flavonoid, was able to confer sensitivity to radiation in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…In the current study, paeonol prevented the elevation of testicular expression of HIF‐1α in comparison with the IR group. Paeonol enhanced the sensitivity of ovarian cancer cells to radiation by downregulating HIF‐1α expression (Zhou, Sun, & Cheng, 2017). Consequently, paeonol, by its antioxidant and anti‐inflammatory effect, could prevent the activation of HIF‐1α in the testes of IR injured rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, paeonol prevented the elevation of testicular expression of HIF‐1α in comparison with the IR group. Paeonol enhanced the sensitivity of ovarian cancer cells to radiation by downregulating HIF‐1α expression (Zhou, Sun, & Cheng, 2017). Consequently, paeonol, by its antioxidant and anti‐inflammatory effect, could prevent the activation of HIF‐1α in the testes of IR injured rats.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells are highly differentiated monolayer cells which cover the surface of the vascular lumen and serve important functions including regulating vascular permeability, maintaining blood flow, and regulating vascular smooth muscle cell proliferation. Endothelial cell apoptosis may increase smooth muscle cell proliferation and migration, enhance blood coagulation, and increase leukocyte infiltration into the endothelium thus leading to endothelial dysfunction [17, 18]. Multiple metabolic disorders in type 2 diabetes mellitus accelerate this pathophysiological process.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the AKT inhibitor, MK-2206, enhanced the radiosensitivity of SiHa cells. It has been reported that the AKT signaling pathway promotes resistance to chemotherapy, radiotherapy and targeted therapy in different types of cancer, including colorectal cancer ( 41 ), non-small cell lung cancer ( 42 ), ovarian cancer ( 43 ) and glioma cell lines ( 44 ). Thus, it was hypothesized that downregulation of GADD45A decreases inactivation of the PI3K/AKT signaling pathway, and contributes to cellular resistance against radiotherapy.…”
Section: Discussionmentioning
confidence: 99%